If it's not what You are looking for type in the equation solver your own equation and let us solve it.
s in (-oo:+oo)
(2/3)*s = 18 // - 18
(2/3)*s-18 = 0
2/3*s-18 = 0 // + 18
2/3*s = 18 // : 2/3
s = 18/2/3
s = 27
s = 27
| 11-10x=42x+19 | | 6x+11=-79-9 | | x+3/4=-1/2 | | x/(-1/6)=6/7 | | 4a-1=2a+27 | | 3x^2+2=59 | | X-15=3x | | x/-1/6=5/7 | | x/-1/6+6/7 | | 1.6s=-8 | | 6(4h-3)=3(5h-3) | | 0.1a-1.09=0.91 | | (1/2)(6x+7)=3x | | -11-6x=-9x | | 1/2z-3/5=12/5 | | 60m=60 | | 13j-4=9j+52 | | 3/5x=7(1-x) | | -79=-5+2(-x-15) | | 3x^3+6x^2+5x=27 | | 2m+1=3m-2 | | 2cos^2x+9cosx-5=0 | | x+x+1/2x+1/4x+1=100 | | 15-4+5=32 | | 5/x=-4/7 | | 2(x+1)=5(1-2x) | | 3(5x-2)=2 | | -6y+13=2y-11 | | 2(4x-3)=6x-(4-x) | | 5x-7y=-10 | | 8x-4x=4 | | y=2x-5/-x-1 |